PENERAPAN STRATEGI PEMBELAJARAN ROTATING TRIO EXCHANGE (RTE) UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA KELAS XI SMA N 14 PEKANBARU - Wisya, Neshia; Irianti, Mitri; Ma’ruf, Zuhdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This research aimed to describe students’ physics learning achievement who learned with Rotating Trio Exchange (RTE) and to determine the significant influence in the sudents’ physics learning achievement among Rotating Trio Exchange (RTE) group with conventional learning group at SMA N 14 Pekanbaru . Type of this research is a quasi-experimental, with Intact Group Comparisson design. The sample of this research is students of XI IPA 4 that is applying Rotating Trio Exchange (RTE) and students of XI IPA 1 that is with conventional learning. The data in this research is a score posttest of physics learning achievement and analysis with descriptive and inferensial analysis. There are significant differences between the outcomes of students in the class by applying Rotating Trio Exchange (RTE) with the class that implements conventional learning. The analysis of data showed absortion of student in the class by applying Rotating Trio Exchange (RTE) is higher than the class that implements conventional learning. The absorption and learning effectiveness in class experiment is 84,85 with good and effective categori.With thus be concluded that the application of Rotating Trio Exchange (RTE) can increasing students’ physics learning achievement at class XI IPA SMA N 14 Pekanbaru in effort and energy topic.